PERNIKAHAN DI BAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA (STUDI KASIS MASYARAKAT SASAK DESA LABUAN TERENG LOMBOK BARAT) - Khairillah Khairillah; Ibnu Jazari; Ach. Faisol (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
Underage marriage is not a new phenomenon, but what must be considered and observed in conducting a marriage like this is that the marriage will form a harmonious household or it will only end in things that are not desirable, because marriage is a relationship that must be fostered seriously and mental maturity and mental and physical readiness both in terms of cyclical and psychological in order to form a harmonious household. In Law number 1 of 1974 concerning marriage, it is explained that the minimum age of 19 years old men and women have reached the age of 16 years old may be married, the minimum age limit for a person to hold a marriage is regulated because to have marriage must have readiness and soul mature body so that the achievement of household harmony as the goal of marriage is the formation of an eternal family. In general, underage marriage does not go well and does not achieve household harmony because in addition to mentally and physically from a cyclical and psychological perspective that is not ready, it is also unprepared to bear the burden of the household and not ready to become parents, due to disharmony the ladder finally the marriage that has been built does not last long or ends with divorce, as happened in the Labuan Tereng Village community whose average marriage because it is not enough according to the Law ends in divorce, even though the marriage is valid according to the Islamic religion , mumayyiz, can be responsible and harmonious and the legal requirements for marriage are fulfilled, but the impact of the marriage also needs to be considered for the good of both parties. Therefore this study aims to find out underage marriage laws, the factors behind the occurrence of underage marriage, and the impact of underage marriages that occur in the Sasak community of Labuan Tereng Village.Kata Kunci: Pernikahan dibawah umur pada masyarakat sasak Desa Labuan Tereng,